2003
DOI: 10.1161/01.hyp.0000050101.90932.14
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Angiotensin II Type 2 Receptor Activates the Kinin/NO System and Inhibits Fibrosis

Abstract: Abstract-We have previously demonstrated that stimulation of the angiotensin (Ang) II type 2 receptor in vascular smooth muscle cells caused bradykinin production by activating kininogenase in transgenic mice. The aim of this study was to determine whether overexpression of AT 2 receptors in cardiomyocytes attenuates Ang II-induced cardiomyocyte hypertrophy or interstitial fibrosis through a kinin/nitric oxide (NO)-dependent mechanism in mice. Ang II (1.4 mg/kg per day) or vehicle was subcutaneously infused in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 43 publications
5
129
1
1
Order By: Relevance
“…A link between AT 2 receptor signaling pathway and stimulation of endothelial bradykinin B 2 receptors (with activation of constitutive nitric oxide synthase) was already described in the heart [29]. Overall, these findings demonstrated that selective AT 2 receptor-stimulation is associated with a negative lusitropic effect modulated by the endocardial endothelium and mediated by bradykinin B 2 receptors through NO release.…”
Section: The Effects Of Angii On Myocardial Relaxationsupporting
confidence: 64%
“…A link between AT 2 receptor signaling pathway and stimulation of endothelial bradykinin B 2 receptors (with activation of constitutive nitric oxide synthase) was already described in the heart [29]. Overall, these findings demonstrated that selective AT 2 receptor-stimulation is associated with a negative lusitropic effect modulated by the endocardial endothelium and mediated by bradykinin B 2 receptors through NO release.…”
Section: The Effects Of Angii On Myocardial Relaxationsupporting
confidence: 64%
“…30,31 This occurs either directly 32 or indirectly through enhanced bradykinin formation 6,33 or increased endothelial NO synthase activity/expression. 34 Thus, AT 2 R may also favorably affect endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Il a été démontré dans plusieurs modèles que la vasodilatation, dépendante de l'endothélium et induite par l'angiotensine II est fortement réduite par un antagoniste du RB2 [10]. De même, la surexpression du récepteur AT2 réduit la fibrose périvasculaire cardiaque induite par la perfusion d'angiotensine II, un effet dépendant du RB2 supprimé par un antagoniste du RB2 [11]. L'activité anti-fibrosante du récepteur AT2 ne repose toutefois pas exclusivement sur l'activation du RB2 car une stimulation de la formation de NO par le récepteur AT2 a été démontrée chez les souris n'exprimant pas le RB2 [12].…”
Section: Rôle De La Bradykinine Dans Le Mécanisme D'action Des Iecunclassified